Artemether-lumefantrine: An oral antimalarial for uncomplicated malaria in children - Adjei, G.O.; Goka, B.Q.; Binka, F.; Al Kurtzhals, J. (Expert Review of Anti-Infective Therapy, 2009)
Artemether-lumefantrine (AL; Coartem®, Riamet®) is the first fixed-dose artemisinin combination therapy (ACT) regimen to be manufactured under Good Manufacturing Practice conditions, and is the most widely adopted ACT regimen used in malaria control programs. AL is approved for the treatment of uncomplicated malaria in adults, children and infants, and as treatment of uncomplicated malaria in nonimmune travelers returning from malarious areas. AL is efficacious for treating uncomplicated malaria in children and the frequency of associated adverse events is not higher than other available ACT regimens. In this review, available evidence on efficacy and safety of AL in the treatment of uncomplicated malaria, with emphasis on children where appropriate, and focusing on characteristics that are potentially important for malaria control policy decisions, are presented and discussed. © 2009 Expert Reviews Ltd.
Keywords: Artemether-lumefantrine; Artemisinin combination therapy; Children; Uncomplicated malaria